التوجيه المدرسي في الجزائر - عليك, نامية; شيباني, ليلى (جامعة الوادي - University of Eloued, 2023)
يعتبر التوجيه المدرسي والمهني جزءا لا يتجزأ من العملية التربوية إذ لا يمكن فصله عنها، فهو احد خدماتها المهمة التي تسعى التربية من خلالها إلى تربية الاختيارات لدى التلاميذ وتنمية مهاراتهم لبناء مشروعهم المستقبلي ، في ظل الإصلاح الحادث والذي يحدث في الجزائر خاصة خلال السنوات الأخيرة. حيث جاءت الدراسة الحالية إلى تحليل واقع التوجيه المدرسي والمهني السائد في المؤسسات التربوية الجزائرية وتطوره، من خلال نظرة نقدية تحليلية للمناشير الوزارية ، وكذا معرفة النظرة الحديثة والنظرة القديمة، مع تسليط الضوء على أهم المشاكل التي يعاني منها التوجيه المدرسي والمهني في الجزائر من خلال إعطاء لمحة واقعية عن التوجيه المدرسي والمهني.Abstract: It is one of the important services through which education seeks to raise the choices of students and develop their skills to build their future project, in light of the reform happening and happening in Algeria, especially in recent years. The present study aims at analyzing the reality of the educational and vocational guidance in the Algerian educational institutions and its development through a critical analytical view of the ministerial dossiers, as well as the knowledge of the modern outlook and the old view, highlighting the most important problems facing the vocational and vocational guidance in Algeria. School and vocational.
قراءة كرونولوجية و تحليلية من الإستقلال إلى الإصلاحات
مقال
Keywords: : التوجيه المدرسي والمهني، المناشير الوزارية، اإلصالح، العملية التربوية; school and vocational guidance, ministerial leaflets, reform, educational process